Analysis of Spatial Interactions in Economic Growth - Widayat, Diva Nur Vitriana; Prianto, Fajar Wahyu; Jumiati, Aisah; Wiryaningtyas, Dwi Perwitasari (Universitas Gorontalo, 2026)
This study aims to analyze the influence of inter regional spatial interactions on economic growth in 35 regencies/cities in East Java, during the 2013–2023 period and using spatial panel estimation. The variables used are Gross Regional Domestic Product (GRDP) at current prices, the Human Development Index (HDI), physical Special Allocation Fund (DAK), and the number of workers. The method used is Spatial Autoregressive Combined (SAC) method with the Fixed Effects Model (FEM) approach. The results of the moran's I test indicate significant spatial autocorrelation on economic growth in East Java. The analysis results show that the HDI and physical DAK variables have a positive and significant effect on economic growth in East Java. Meanwhile, the number of workers variable have a positive but insignificant effect on economic growth in East Java in this study.